Study of prognostic significance of platelet count as a predictor of severity of preeclampsia - Khan, Saba; Singh, Amrita; Vatsal, Priti; Akhtar, Kafil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pre-eclampsia is a pregnancy-specific syndrome, recognised from antiquity as a leading cause of maternal and perinatal mortality, and it accounts for almost 15% of pregnancy associated death. Hence, the current study was planned to assess the role of platelet count as a predictor of the severity of preeclampsia and its prognosis. Methods: In this retrospective analytical study, a total of 100 pregnant women with preeclampsia were included and divided into two groups of non-severe and severe. Demographic data, socio-economic status, period of gestation and platelet count were recorded and compared. Results: The average age of patients was 27.07±5.14 years, with no significant difference between patients based on preeclampsia severity. Most of the patients were multigravida females (69%). The distribution based on the socio-economic status was similar, with no significant difference (p>0.05). The average period of gestation was 36.01±3.41 weeks in the study. The average platelet count of patients with severe preeclampsia at the time of admission was seen to be lower compared to the non-severe patients. A ROC curve analysis was done to assess the ability of platelet count to differentiate severe PWE from non-severe PE. The area under the curve was high at 0.879. The LSCS rate was 54% in the study, followed by Pre-term birth seen in 48% of patients. There was no significant difference between the two groups in terms of maternal outcome parameter-based distribution. The proportion of patients with APGAR score <7 at 5 minutes was significantly higher in the non-severe PE group. It was seen that preeclamptic patients were associated with a significantly higher prevalence of pre-term birth and Ante partum haemorrhage (APH). Conclusions: Platelet count is an accurate predictor of severe preeclampsia in pregnant females. The patients with low platelet counts were associated with significantly higher adverse pregnancy outcomes, as suggested by a significantly higher prevalence of pre-term birth, APH and rate of LSCS.